An Aniline-Mediated Regioselective Synthesis of Quinoxalin-2-ones via the Condensation of α-Ketimine Esters with 2-Aminoanilines - Huynh, Huy V.; Çalimsiz, Selçuk; Wangun, Hilaire V. Kemami; Rainey, Trevor J.; McGinitie, Teague M.; Liao, Xiaoming; Yu, Lizhi (Synthesis, 2018)
A highly regioselective method for the condensation of α-ketimine esters with 2-aminoanilines for the construction of quinoxalin-2-one derivatives is described. The substrate scope with 2-aminoaniline derivatives and different α-keto esters is explored with yields ranging from 44 to 90% and typical isolated regioselectivities between 6.4 to >25:1.
Keywords: quinoxalin-2-ones; 2-aminoanilines; α-ketimine esters; one-pot synthesis; transimination; regioselectivity